Isolated but not combined ergogenic effects of caffeine and L-arginine during an isokinetic knee extension - Zart, Sebastian; Brachtendorf, Maximilian; Becker, Stephan; Fröhlich, Michael (Frontiers in Nutrition, 2024)
Introduction The use of single supplements as ergogenic aids to enhance performance in strength-oriented sports is widespread among athletes (74%). The aim of this study was to increase knowledge about the combined effects of caffeine and L-arginine dietary supplements on performance. Methods In this double-blind, randomized and counterbalanced crossover study, 29 participants (age: 23.2 ± 3.6 yr.; height: 181.0 ± 7.6 cm; weight: 77.0 ± 8.8 kg) each underwent six trials. In each trial performance tests were conducted to examine the effects of the supplement combinations on maximum (NmMax) and averaged torque (NmM), maximum (JMax) and averaged work (JM), the blockwise mean values of torque and work, and rate of perceived exertion (RPE) during an isokinetic leg extension task (90°·s−1) with the right leg for two sets of 40 repetitions and a set rest of 3 min on a dynamometer. The first and second trials were used to familiarize the participants with the movements in the dynamometer and no supplements were taken. After this 2-week pre-test trial, the supplement combinations of placebo/placebo, caffeine/placebo (5 mg·kg−1), L-arginine/placebo (0.15 g·kg−1), and caffeine/L-arginine (5 mg·kg−1 + 0.15 g·kg−1) were ingested. Results The main finding of this study is the absence of an ergogenic effect of the combined supplements caffeine and L-arginine during voluntary maximal isokinetic leg extensions, although an increase of 3.5% was noted for Nmmax compared to the placebo trial. However, the administration of caffeine was able to increase the NmMax of the quadriceps femoris muscle about 5.1% (p = 0.043). In addition, caffeine (4.2%, p = 0.026) and also L-arginine (4.2%, p = 0.040) significantly increased NmM over a complete set. No single or combined supplement had an effect on muscle fatigue looking at the blockwise mean values of torque and work or RPE (all p > 0.05). Conclusion The combination of caffeine and L-arginine was not superior to the isolated intake of both supplements in a strength-based exercise and a synergistic effect was absent.